Studiu de evaluare a activității sindicale în cadrul Bibliotecii Municipale „B.P. Hasdeu” (Chestionar 2024): o abordare postumanistă - GUMENI, Svetlana (BIBLIOPOLIS, 2025)
The study conducted in summer 2024, as part of the Trade Union School, assesses employees’ perception of union activity at the B.P. Hasdeu Municipal Library. The questionnaire, completed by 64 participants, revealed critical issues such as insufficient communication with the union, poor working conditions, understaffing, and inadequate pay. Respondents expressed expectations for stronger union involvement in defending workers’ rights and improving financial transparency. Recommendations included infrastructure investment, awareness sessions, fostering a respectful and motivating work environment, and fairer distribution of benefits. The report signals an urgent need for union and management reform, offering actionable proposals to enhance librarians’ professional well-being.